CORPORATE CAPITAL STRUCTURE DETERMINANTS OVER THE LATEST GLOBAL CRISIS: THE CASE OF POLAND - Andrzej CWYNAR; Wiktor CWYNAR; Piotr ORATOWSKI; Marta STACHOWICZ (Modern Management Review, 2016)
Capital structure decisions in firms and factors determining them still belong to the most challenging research issues that deserve more empirical studies. The recent global crisis has put the subject into a new perspective as it was clearly related to debt issues. Using panel data and multi factor regression procedure we investigated the diversified sample of almost 4000 public and non-public firms operating in Poland over 2006–2011 period to verify the degree to which the most significant traditional firm-specific factors explain their capital structures. Specifically, our study was aimed at examining the potential differences in the investigated relationships in the pre-crisis years as compared to the crisis ones. We confirmed the previous findings of other researchers concerning the impact profitability and size have on leverage. We showed also that the latest global crisis did not influence significantly capital structure selection patterns observed in our sample despite visible changes in the financial performance of the investigated firms. However, our evidence is inconclusive in terms of the verification of two classic capital structure theories: trade-off and pecking order. Some of our empirical findings may be of a practical importance as they can indicate some desired rearrangements in the institutional environment of firms, including financial markets, and suggest the appropriate directions for the potential policy programs.